Southern Anthropology - a History of Fison and Howitt’s Kamilaroi and Kurnai - Gardner, Helen. author. aut Link
XX, 329 p.
Keywords: Southern Anthropology, the history of Fison and Howitt's Kamilaroi and Kurnai is the biography of Kamilaroi and Kurnai (1880) written from both a historical and anthropological perspective. Southern Anthropology investigates the authors' work on Aboriginal and Pacific people and the reception of their book in metropolitan centres.